How to Cheat in Photoshop CS4 - 5 - Caplin, Steve (Elsevier, 2011)
Do you want to let your creativity run wild in Photoshop, but don't know where to start? Are you having trouble getting your ideas out of your head and onto the screen? Do you need your photomontages to look convincing... and fast?